Teachers as market influencers: Towards a policy framework for teacher brand ambassador programs in K-12 schools - Saldaña, Christopher Michael; Welner, Kevin; Malcolm, Susan; Tisch, Eleanore (Education Policy Analysis Archives, 2021)
Marketing in schools has a new twist, and teachers are at the center. Corporate firms, particularly those producing education-technology products, have contracted with teachers to become so-called brand ambassadors and micro-influencers. Scant research, however, has examined these brand ambassador arrangements, leaving policymakers uninformed about the implications for students, teachers, and schools. In this article, we delve into what it means to be a teacher brand ambassador (TBA) and micro-influencer by examining the context in which these programs arose and studying current examples of TBA and TBA-like programs offered by Google, Amazon, Apple, and Microsoft. We review how these recent instantiations of marketing compare to similar practices used to sell prescription drugs to and through doctors, and we explore ethical, legal and policy issues associated with the recruitment and contracting of teachers as brand ambassadors. Further, anticipating the need for the protection of students’ and teachers’ interests as TBA programs grow as a presence in public schools, we offer a model policy framework to regulate the use of these marketing practices in schools.